PELAKSANAAN PROGRAM SEHATI SEBAGAI UPAYA PENURUNAN ANGKA KEMATIAN BAYI DI DESA KEPUHPANDAK KECAMATAN KUTOREJO KABUPATEN MOJOKERTO - Ulum Rokhmat Rokhmawan; Indasah (Jurnal Pengabdian Masyarakat, 2024)
Infant mortality is a death that occurs in children before the age of 1 year which occurs due to several factors. Infant mortality is one of the important indicators of public health and is associated with maternal mortality. Referring to the problem, the SEHATI Program (Healthy Tuesday to Prevent Maternal, Infant and Stunting Events) Program activities were initiated by the Mojokerto Regency Health Office which was monitored directly by the Mojokerto Regent. This effort is able to improve the ability of cadres to assist breastfeeding and foster families to be able to provide nutritious food to prevent stunting from an early age.